Does transformational leadership, empowerment, and work ethic effect on job enrichment and employee performance? - Gede, I Komang; Brahmasari, Ida Aju; Ardiana, I Dewa Ketut Raka (International research journal of management, IT and social sciences, 2022)
This study aims to prove and analyze the effect of transformational leadership, empowerment, work ethic on job enrichment and employee performance. The object and location of this research is the Village Credit Institution (LPD) as a financial institution owned by Pakraman Village in 9 districts/cities in Bali. The sampling technique is based on the proportionate random sampling method, which is taking samples from each LPD area of ??the Traditional Village randomly and proportionally, because the population members are homogeneous. The size of the sample is 300 people. Based on the results of the analysis and hypothesis testing that have been carried out, the results of this study indicate that of the 7 hypotheses proposed, all of them are proven true or supported by empirical facts, which predict a significant direct effect between transformational leadership factors, empowerment, work ethic and employee performance.